Normal Ventricular Functional Reference Parameters on Magnetic Resonance Imaging in Healthy Children - Doughanji, Roula; Elmali, Muzaffer; Sungur, Metin; Azak, Emine; Baysal, Kemal; Celenk, Cetin (Current Medical Imaging, 2013)
We aimed to research right and left ventricular functional reference values on magnetic resonance imaging in healthy children. Echocardiographically normal sixty healthy children were performed cardiac MRI between January 2009 and June 2010. Biventricular volumes, left myocardial mass, septal thickness, diameter of the ascending aorta and main pulmonary artery were calculated. It was investigated whether there was a difference or not between ventricular volumes and sexes, and the relationship age and body surface area with functional parameter results. The minimum, maximum, mean values of every parameters were determined in all children, boys, girls, and in the groups of age 8-12 and 13-18. There was a statistically significant difference in the left ventricular end-systolic diameter results between the sexes. There were statistical significant differences in parameter results except biventricular cardiac output and ejection fraction, right ventricular end-diastolic and end-systolic diameter between the age groups when the children were grouped as 8-12 and 13-18 years by ignoring their sexes. When it was compared the mean value of normal functional parameters after normalized to body surface area; the mean values of all parameters were higher in males, but there was a significant difference in only between right ventricular end-diastolic volumes. Biventricular cardiac output mean values were higher in the age group of 8-12 years. Consequently, we determined the mean, minimum, and maximum values of normal ventricular volumes, left myocardial mass, septal thickness, diameter of the ascending aorta and main pulmonary artery in the 8-18 age group to be used as a reference in all diagnostic and follow-up stage.
Keywords: SSFP